Effect of physical and academic stress on illness and injury in division 1 college football players - Mann, J. B.; Bryant, K. R.; Johnstone, B.; Ivey, P. A.; Sayers, S. P. (The Journal of Strength and Conditioning Research, 2016)
Stress-injury models of health suggest that athletes experience more physical injuries during times of high stress. The purpose of this study was to evaluate the effect of increased physical and academic stress on injury restrictions for athletes (n = 101) on a division I college football team. Weeks of the season were categorized into 3 levels: high physical stress (HPS) (i.e., preseason), high academic stress (HAS) (i.e., weeks with regularly scheduled examinations such as midterms, finals, and week before Thanksgiving break), and low academic stress (LAS) (i.e., regular season without regularly scheduled academic examinations). During each week, we recorded whether a player had an injury restriction, thereby creating a longitudinal binary outcome. The data were analyzed using a hierarchical logistic regression model to properly account for the dependency induced by the repeated observations over time within each subject. Significance for regression models was accepted at p = 0.05. We found that the odds of an injury restriction during training camp (HPS) were the greatest compared with weeks of HAS (odds ratio [OR] = 2.05, p = 0.0003) and LAS (OR = 3.65, p < 0.001). However, the odds of an injury restriction during weeks of HAS were nearly twice as high as during weeks of LAS (OR = 1.78, p = 0.0088). Moreover, the difference in injury rates reported in all athletes during weeks of HPS and weeks of HAS disappeared when considering only athletes that regularly played in games (OR = 1.13, p = 0.75) suggesting that HAS may affect athletes that play to an even greater extent than HPS. Coaches should be aware of both types of stressors and consider carefully the types of training methods imposed during times of HAS when injuries are most likely.